13C NMR spectroscopy applications to brain energy metabolism - Rodrigues, Tiago B.; Valette, Julien; Bouzier-Sore, Anne-Karine (Frontiers in Neuroenergetics, 2013)
13C Nuclear Magnetic Resonance spectroscopy is the method of choice for studying brain metabolism. Indeed, the most convincing data obtained to decipher metabolic exchanges between neurons and astrocytes have been obtained using this technique, thus illustrating its power. It may be difficult for non-specialists, however, to grasp the full implication of data presented in articles written by spectroscopists. The aim of the review is, therefore, to provide a fundamental understanding of this topic to facilitate the non-specialists in their reading of this literature. In the first part of this review, we present the metabolic fate of 13C-labelled substrates in the brain in a detailed way, including an overview of some general neurochemical principles. We also address and compare the various spectroscopic strategies that can be used to study brain metabolism. Then, we provide an overview of the 13C Nuclear Magnetic Resonance experiments performed to analyse both intracellular and intercellular metabolic fluxes. More particularly, the role of lactate as a potential energy substrate for neurons is discussed in the light of 13C Nuclear Magnetic Resonance data. Finally, new perspectives and applications offered by 13C hyperpolarization are described.